Anti‐Metastatic Effect of Supercritical Extracts from the Citrus hassaku Pericarp via Inhibition of C‐X‐C Chemokine Receptor Type 4 (CXCR4) and Matrix Metalloproteinase‐9 (MMP‐9). (17th March 2014) - Kim, Chulwon; Kim, Dongmin; Nam, Dongwoo; Chung, Won‐Seok; Ahn, Kyoo Seok; Kim, Sung‐Hoon; Choi, Seung‐Hoon; Shim, Bum Sang; Cho, Somi K.; Ahn, Kwang Seok
<x xml:space="preserve">Abstract</x> The fruit of hassaku (Citrus hassaku Hort. ex Tanaka) is locally known as phalsak in Korea. Recently, the fruit extract has been known to exhibit in vivo preventive effects against UVB‐induced pigmentation, antiallergic activity, and enhancement of blood fluidity. However, the exact mechanisms of how supercritical extracts of phalsak peel (SEPS) inhibits tumor metastasis and invasion are still not fully understood. We found that SEPS could downregulate the constitutive expression of both CXCR4 and HER2 in human breast cancer MDA‐MB‐231 cells as compared with other cells. SEPS also suppressed matrix metalloproteinase‐9 (MMP‐9) expression and its enzymatic activity under non‐cytotoxic concentrations. Neither proteasome inhibition nor lysosomal stabilization had any effect on the SEPS‐induced decrease in CXCR4 expression. A detailed study of the underlying molecular mechanisms revealed that the regulation of the downregulation of CXCR4 was at the transcriptional level, as indicated by downregulation of mRNA expression, suppression of NF‐κB activity, and inhibition of chromatin immunoprecipitation activity. Suppression of CXCR4 expression by SEPS correlated with the inhibition of CXCL12‐stimulated invasion of MDA‐MB‐231 cells. Overall, our results indicate, for the first time, that SEPS can suppress CXCR4 and MMP‐9 expressions through blockade of NF‐κB activation and thus has the potential to suppress metastasis of breast cancer. Copyright © 2014 John Wiley & Sons, Ltd.